Tinjauan Yuridis terhadap Pemeriksaaan Saksi dalam Perkara Pidana pada Persidangan secara Teleconference di Masa Pandemi Covid-19 - Kurnia Aji Nugroho (Postgraduate University of Merdeka Malang, 2022)
This study aims to examine the validity of remote witness examination (teleconference) at trials during the Covid-19 pandemic and the evidentiary power of remote witness examination (teleconference) at court hearings. This study uses normative legal research methods. The results showed that the use of teleconferences in criminal trials is legal / valid in order to obtain material truth, by applying the provisions of the Criminal Procedure Code in principle not violating the provisions of the applicable Law and as long as the witness meets the following conditions: a) Witnesses must first take an oath. b) Witness testimony is stated orally through audio-visual communication devices/ teleconference at the trial. c) The content of the testimony must be about what the witness saw, heard, and experienced, and mention the reason for the knowledge. d) The witness testimony is consistent with each other. The evidentiary power of testimony through video conferencing in criminal trials is strong.DOI: https://doi.org/10.26905/mlj.v3i2.9213